EVALUATION OF IRON ACCUMULATION DURING CHILDHOOD CANCER TREATMENT - Şule Çalışkan Kamış; Metin Çil; Begül Yağcı; Barbaros Şahin Karagün (Hematology, Transfusion and Cell Therapy)
Objective: Iron overload is a major concern in pediatric oncology, particularly with frequent blood transfusions. Although serum ferritin levels are commonly used as a marker, cardiac and hepatic T2* MRI is the gold standard for accurate assessment. This study aimed to evaluate the relationship between serum ferritin levels and T2* MRI values in pediatric cancer patients, focusing on cases with ferritin levels exceeding 1000 mcg/L. Methodology: This prospective study included pediatric patients aged 10-25 diagnosed with malignancies at Adana City Training and Research Hospital from June 2023 to December 2024. Ferritin and C-reactive protein (CRP) levels were measured during non-infectious periods. Elevated ferritin was confirmed if CRP was also raised. Data on transfusions and ferritin levels were collected at 3, 6, and 12 months post-diagnosis. Patients with ferritin levels above 1000 mcg/L underwent cardiac and hepatic T2* MRI to assess the need for iron chelation therapy. Results: A total of 28 patients (median age: 14 years) were analyzed, with 12 females and 16 males. The median ferritin level at diagnosis was 32.5 mcg/L. Significant associations were found between transfusion frequency and ferritin levels over 1000 mcg/L within 3 months (p=0.029) and annually (p=0.001). Three patients had ferritin levels above 1000 mcg/L: two with acute lymphoblastic leukemia (ALL) and one with non-Hodgkin lymphoma (NHL). One patient died, another received a bone marrow transplant, and the third had normal cardiac but moderate hepatic iron levels. In one case, ferritin dropped below 1000 mcg/L without chelation by 12 months. Elevated ferritin in the transplant patient was likely related to the procedure. Conclusion: Iron overload is a significant challenge in pediatric cancer, particularly during transplants. Early monitoring and timely chelation can help manage this risk. Future research should focus on optimizing iron management strategies in this vulnerable population.